The odd moments of ranks and cranks - Chan, Song Heng (2013)
In this paper, we modify the standard definition of moments of ranks and cranks such that odd moments no longer trivially vanish. Denoting the new k-th rank (resp. crank) moments by (resp. ), we prove the following inequality between the first rank and crank moments.